Catalyzing Transformations to Sustainability in the World's Mountains. Issue 5 (25th May 2019) - Klein, J. A.; Tucker, C. M.; Nolin, A. W.; Hopping, K. A.; Reid, R. S.; Steger, C.; Grêt‐Regamey, A.; Lavorel, S.; Müller, B.; Yeh, E. T.; Boone, R. B.; Bourgeron, P.; et al.
Abstract: Mountain social‐ecological systems (MtSES) are vital to humanity, providing ecosystem services to over half the planet's human population. Despite their importance, there has been no global assessment of threats to MtSES, even as they face unprecedented challenges to their sustainability. With survey data from 57 MtSES sites worldwide, we test a conceptual model of the types and scales of stressors and ecosystem services in MtSES and explore their distinct configurations according to their primary economic orientation and land use. We find that MtSES worldwide are experiencing both gradual and abrupt climatic, economic, and governance changes, with policies made by outsiders as the most ubiquitous challenge. Mountains that support primarily subsistence‐oriented livelihoods, especially agropastoral systems, deliver abundant services but are also most at risk. Moreover, transitions from subsistence‐ to market‐oriented economies are often accompanied by increased physical connectedness, reduced diversity of cross‐scale ecosystem services, lowered importance of local knowledge, and shifting vulnerabilities to threats. Addressing the complex challenges facing MtSES and catalyzing transformations to MtSES sustainability will require cross‐scale partnerships among researchers, stakeholders, and decision makers to jointly identify desired futures and adaptation pathways, assess trade‐offs in prioritizing ecosystem services, and share best practices for sustainability. These transdisciplinary approaches will allow local stakeholders, researchers, and practitioners to jointly address MtSES knowledge gaps while simultaneously focusing on critical issues of poverty and food security. Plain Language Summary: Mountain ecosystems and the human communities that inhabit them deliver critical resources—such as fresh water and timber—to over half the planet's human population. Despite their importance, there has been no global assessment of threats to mountain systems, even as they face unprecedented challenges to their sustainability. With survey data from 57 mountain sites worldwide, we test our understanding of the types of stresses that are threatening mountain systems as well as the resources and benefits that come from mountains. We find that mountain systems worldwide are experiencing both gradual and abrupt climatic, economic, and governance changes. One of the most ubiquitous challenges facing mountain systems is that policies directly affecting mountain systems are being made by those living outside of the mountains themselves. Mountains that support primarily subsistence‐oriented livelihoods in the developing world, especially mixed agriculture and animal husbandry systems, deliver abundant services but are also most at risk. Addressing the complex challenges facing mountain systems will require partnerships among researchers, stakeholders, and decision makers to jointly identify the types of futures they desire and the actions to achieve these. This approach will address knowledge gaps in mountains while simultaneously focusing on critical issues of poverty and food security. Key Points: Mountain social‐ecological systems (MtSES) worldwide face climatic, economic, and governance threats; policies made by outsiders are a critical challenge Mountains that support subsistence‐oriented livelihoods deliver abundant cross‐scale ecosystems services, but these MtSES are also most threatened Addressing threats to MtSES requires the united effort of policymakers, land users, scientists, and practitioners at local to global scales